Efeitos do turno de rega e cobertura morta na cultura do alho na serra da Ibiapaba, Ceará. I. Umidade e temperatura do solo Irrigation frequency and mulching effects on gerlic culture in Ibiapaba region, State of Ceará, Brazil. I. Soil moisture and temper (Revista Ciência Agronômica, 2023)
RCA